Growth and nutrient content of black pepper (Piper nigrum L.) cuttings as influenced by inoculation with biofertilizers - K S Krishnamurthy, K Kandiannan, K Sivaraman, M Anandaraj (Journal of Spices and Aromatic Crops, 2000)
Experiments conducted to test the effect of Azospirillum, phosphobacteria and vesicular arbuscular mycorrhiza on growth and nutrient content of black pepper (Piper nigrum) cuttings indicated that growth parameters were on par with control when these three biofertilizers were applied individually, but their combination enhanced growth significantly over control. Inoculation with a combination of two / three biofertilizers enhanced plant height, leaf area, biomass and dry matter production and nutrient content significantly over uninoculated control.